Late recovery after traumatic, anoxic, or hemorrhagic long-lasting vegetative state - Estraneo, A; Moretta, P; Loreto, V; Lanzillo, B; Santoro, L; Trojano, L (Neurology, 2010)
Late recovery of awareness in vegetative state (VS) is considered as an exceptional outcome, and has been reported prevalently after traumatic brain injury (TBI). The present prospective study aimed to verify frequency of late recovery (later than 1 year postonset in TBI and 3 months postonset in patients without TBI) of responsiveness and consciousness in traumatic and nontraumatic long-lasting (more than 6 months after onset) VS. Fifty inpatients with long-lasting VS (36% TBI, 36% hemorrhagic, and 28% anoxic) were enrolled and followed up for a mean of 25.7 months from onset (5 patients for more than 4 years). Level of responsiveness and functional disability were evaluated by means of validated scales (Coma Recovery Scale-Revised and Disability Rating Scale). At the end of the study, 21 patients (42%) had died, 17 patients (34%) were in VS, and 2 patients with TBI (4%) had recovered responsiveness within 12 months postonset. The remaining 10 (20%) patients with TBI and patients without TBI showed late recovery of responsiveness; 6 of them (12%) further progressed to consciousness. Late recovery was significantly associated with younger age and was relatively more frequent in TBI. Functional abilities were severely impaired in all patients. This clinical study demonstrates that late recovery of responsiveness and consciousness is not exceptional in patients with traumatic and nontraumatic VS, although with residual severe disability.